Mitochondrial DNA transfer between malignant cells and T lymphocytes shapes the cancer-immunity dialogue - Liwei Zhao; Peng Liu; Oliver Kepp; Guido Kroemer (OncoImmunology)
Nonmutated mitochondrial DNA (mtDNA) from T lymphocytes can be incorporated into cancer cells bearing mutated mtDNA to repair their bioenergetic deficiency. However, a recent paper by Ikeda et al. indicates that mutated mtDNA from malignant cells can also be transferred into tumor-infiltrating T lymphocytes to subvert their function in cancer immunosurveillance.